Total-body PET/CT metabolic response in esophageal squamous cell carcinoma - Yang, Runjun; Lu, Xinyi; Tang, Wenxin; Nardo, Lorenzo; Xie, Yunze; Al-Ibraheem, Akram; Zhang, Lichao; Zhao, Wenjin; Rominger, Axel; Tan, Lijie; Tang, Han; Muhammad Fuad, Ida Nur Syafinaz; et al. (W.B. Saunders, 2026)
Esophageal squamous cell carcinoma (ESCC) exhibits heterogeneous responses to neoadjuvant therapy, necessitating early and accurate assessment. [18F]fluorodeoxyglucose ([18F]FDG) PET/CT enables quantitative assessment of tumor glucose metabolism, correlating with pathological remission and long-term outcomes, while [18F] or [68Ga]Ga-labeled fibroblast activation protein inhibitor (FAPI) PET/CT evaluates stromal metabolism, providing complementary information. Total-body PET/CT (uEXPLORER, United Imaging Healthcare Co.Ltd., Shanghai, China) with 194-cm long-axial field-of-view (LAFOV) offers long axial coverage, up to 68-fold higher sensitivity than conventional systems. It enables low-dose, rapid imaging, dynamic whole-body parametric imaging, and improves detection of small, low-uptake lesions as well as metastatic lesions in the distal upper or lower extremities in a single bed position. Delayed and dual-time imaging protocols, alone and/or combined with deep learning–based synthetic CT, further improve lesion detectability while minimizing radiation exposure. This narrative review summarizes evidence from conventional PET/CT studies, highlights the technical and clinical advantages of total-body PET/CT, and discusses its feasibility, quantitative capabilities, and potential to guide response-adapted management in ESCC based on our institutional experience.